BAKERY CONFECTIONERY TOBACCO WORKER INTL - DECONCINI,J (Tufts Archival Research Center, 2007)
Letter from John DeConcini International President of the Bakers Confectioners and Tobacco Workers' (BC&T) Union, to Edward J. Carlough, president of the Sheet Metal Workers International Union regarding the formation of the Labor Management Committee (LMC). Appeals to Carlough on the basis that both unions are intricately involved with the tobacco industry and that it is in their best interest to support them. Invites Carlough to become a member of the LMC.